The Influence of the Conformity Level of Fire Alarm Installations, Fire Detectors, and Portable Fire Extinguishers on the Fire Protection System - Anton Abdullah; Cris Kuntadi (Dinasti International Journal of Education Management And Social Science, 2023)
Abstract: This article aims to review the literature on the effect of the suitability level of fire alarm installations, fire detectors, and portable fire extinguishers on fire protection systems in buildings. Previous research is needed to support or oppose the new hypothesis. From the research conducted, it was found that the suitability level of fire protection equipment installation is very important to increase the effectiveness of the fire protection system. Appropriate fire alarms and fire detectors, as well as suitable portable fire extinguishers, are required to detect fires as quickly as possible and provide a rapid and appropriate response to address the fire. In addition, proper maintenance of fire protection equipment is also required to ensure optimal system performance. The results of this article show that: 1) The suitability level of the fire alarm installation affects the fire protection system; 2) The suitability level of the fire detector installation affects the fire protection system; and 3) The suitability level of portable fire extinguisher installation affects the fire protection system. Increasing the suitability of the installation of fire protection equipment in buildings, can increase the effectiveness of the fire protection system and minimize the risk of fire.